1997
DOI: 10.1103/physrevlett.79.3166
|View full text |Cite
|
Sign up to set email alerts
|

Energy Velocity of Diffusing Waves in Strongly Scattering Media

Abstract: Measurements of the diffusive transport of multiply scattered ultrasonic waves show that the energy velocity is very similar in magnitude and frequency dependence to the group velocity. Our data are accurately described using a theoretical model that accounts for the renormalization of scattering by the coupling between neighboring scatterers, quantitatively predicting the scattering delay that causes the strong frequency dependence of these velocities seen in our experiments. This gives a unified physical pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 14 publications
(33 reference statements)
2
49
5
Order By: Relevance
“…In Fig. 1, we present the results of y E as a function of frequency for the acoustic case for three concentrations, confirming that the behavior observed by Schriemer et al [1] is qualitatively reproduced. In addition, the new effective medium theory gives the correct long-wavelength limit for the effective dielectric constant e e for both the scalar and EM cases.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…In Fig. 1, we present the results of y E as a function of frequency for the acoustic case for three concentrations, confirming that the behavior observed by Schriemer et al [1] is qualitatively reproduced. In addition, the new effective medium theory gives the correct long-wavelength limit for the effective dielectric constant e e for both the scalar and EM cases.…”
supporting
confidence: 76%
“…For larger f s the dips are smeared out, as observed in several experiments. Schriemer et al [1] concluded that our new effective medium approach gives the wrong results for acoustic waves, since their measurements indicate considerable structure in y E at high f s . However, their setup corresponds to low dielectric scatterers in a high dielectric background.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Anderson localization of light has recently indeed been observed [2]. By contrast, to date only a few experiments on sound propagation in the strongly scattering regime have been performed [3][4][5][6]. However, these experiments yielded astonishing results.…”
Section: Sound Propagation In Suspensions Of Colloidal Spheres With Vmentioning
confidence: 85%